ANALISIS PENERIMAAN FITUR SHOPEE PAYLATER PADA APLIKASI SHOPEE MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Fachry Nurfaidzi; Ismi Kaniawulan; Dayan Singasatia (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
Commercial organizations or companies must use e-commerce to remain competitive on a worldwide scale. Shopee is the most popular e-commerce, the features provided are related to the payment system, is the SPaylater feature. The paylater that is widely used throughout 2021 is Shopee Paylater as much as 78.4%. Applying the Technology Acceptance Model (TAM) method with four constructs namely Perceived usefulness, Perceived ease of use, Attitude to use, Actual system use, and one external variable namely Trust, this study aims to find out what influences the acceptance of the Spaylater feature in the Shopee application. Utilizing the structural equation model (SEM) as a hypothesis test. The findings from this study found a significant positive effect between Trust on Perceived Ease of Use and Perceived Usefulness. Then found a significant positive effect between Perceived Ease of Use, Perceived Usefulness on Attitude Toward Using and Attiude Toward Using a significant positive effect on Actual System Use.